Gestión pedagógica en Educación Intercultural Bilingüe de los niños de inserción al proceso semiótico. - Curicho Chugchilán, Norma Graciela (2021)
Strengthening pedagogical management in intercultural bilingual education (IBE) for children is aimed to insertion into the semiotic process (ISP) education with complete freedom where they develop emotional aspects, social, motor, cognitive and language; either individually or collectively at the “Sergio Núñez” Intercultural Community Bilingual Education Center with theoretical perspectives that allows us to understand the importance of pedagogical management in education validated by the results of didactic guides application as a research work proposal directed to teachers and developed through Intercultural bilingual education system model (IBESM). The EIB is a community contribution is given to the indigenous peoples life and Ecuadorian society in general, from the critical perspective of educational reality and the construction of an own and liberating education; with the use of mother´s tongue as the main language in education, recognizing and strengthening the organization in rural communities, where knowledge of community life is the fundamental pillars in educational processes; that is to say, respond to the needs of education according to the context, since it gives the epistemic importance and previous practice of the students; through dialogue of knowledge, analysis, creativity and criticism to end with western alignment.